Ecosystems of Choice: On Some Limitations of Rational Choice Theory and a Strategy for Overcoming Them - Kurakin, Dmitry; Latypov, Ilias (Journal of Economic Sociology, 2023)
This article aims to revise and refine the concept of choice in sociology, primarily in the context of inequality studies. Despite the criticisms and known limitations of rational choice theories, alternative theoretical perspectives on choice often remain marginalized, especially in empirical studies. Recent advances in sociological theory and the sociology of culture and cognition allow problematizing this influential approach, and building a strategy to overcome its limitations. First, traditional approaches to decision-making presume a deficit, whereas excess often dominates within contemporary social life. Second, in addition to rationality and the actions of individuals themselves, choice is often associated with a certain amount of luck. In the studies of inequality, luck emerges as one of the key factors of choice, since the privileged and the unprivileged differ greatly in their ability to overcome or minimize the consequences of setbacks, and conversely to enjoy the fortunate events. A third argument for reconsidering the problem of choice arises from advancements in neuro-cognitive sciences. Numerous studies conducted in recent decades have shown that most of our decisions defy the principles of rational choice theory. The previously dominant computational theory of cognition has been replaced by distributive models that extend cognitive processes beyond the confines of the brain. Finally, contemporary sociological studies of culture and inequality turn their attention to the cultural processes that shape choice and their emotional dimension. The authors conclude with a strategy of going beyond atomic acts of choice to encompass the entire “ecosystems” of choice.